The Link Between Disability Adaptation and Subjective Well-Being (Empirical Evidence from Indonesia) - Subanti, Sri; Hakim, Arif Rahman; Pratiwi, Hasih; Susanto, Irwan; Lestari, Etty Puji; Ihzarani, Ulya Medina (RSF Conference Series: Business, Management and Social Sciences, 2024)
Persons with disabilities will experience life in ways that are not typical because they perceive the detrimental effects of declining or nonexistent material well-being as they become older. As there is not much socioeconomic literature on the subject, this study looks at the different types of disabilities and how they affect people’s subjective well-being in a certain period of time. This study accommodates disabilities such as hearing loss, impaired hand and foot movement, difficulty communicating, and incapacity to care for oneself. We use household and individual data to collect disability and subjective well-being information, apply an adaptation model, and empirically examine the link between the two. Our findings show that the well-being of households with disabled members is lower, although they can adapt over time to the negative effects of disability on well-being. With the exception of people who suffer from vision and hearing impairments, material well-being is not usually positively correlated with disability. As a result, stronger adaptation may help the household welfare level to recover prior to disability (pre-disability). This indicates that if adaptation exists, the negative impacts of disability will tend to decrease with time. We suggest that the government needs to give their daily activities more consideration.